Compassion Fatigue Among Pediatric Healthcare Providers. Issue 3 (May 2015) - Branch, Carole; Klinkenberg, Dean
Abstract: Background: Compassion fatigue is a term used to describe the unique stressors affecting people in caregiving professions. Purpose: For nurses and other direct care providers, the impact of compassion fatigue may result in stress-related symptoms, job dissatisfaction, decreased productivity, decreased patient satisfaction scores, safety issues, and job turnover. Those who care for seriously ill children and their families are at increased risk for compassion fatigue. Constant exposure to children who are suffering, in combination with work place stressors and personal issues, may contribute to the development of compassion fatigue. Methods: The Professional Quality of Life Scale Version 5 was used to determine the risk for compassion fatigue among 296 direct care providers at St. Louis Children's Hospital. Results: Compassion satisfaction, burnout, and secondary traumatic stress scores did not differ by age, work category, level of education, or work experience. There were, however, significant differences in scores as a function of nursing unit. Nurses who work in the pediatric intensive care unit reported lower compassion satisfaction scores, and higher burnout and secondary traumatic stress scores. Clinical Implications: Results demonstrated the risk for compassion fatigue and provided data necessary to support development of a compassion fatigue program for direct care providers. Abstract : Pediatric nurses caring for chronically and acutely ill children are at increased risk for developing compassion fatigue. This study evaluated compassion fatigue of pediatric nurses and allied health professionals in an academic pediatric hospital. Based on results, a program that includes recognition of signs of burnout and compassion fatigue and self-help measures has been developed and implemented at the hospital.